Descriptive epidemiology of Crimean-Congo Hemorrhagic Fever (CCHF) in Afghanistan: Reported cases to National Surveillance System, 2016–2018. (November 2019) - Sahak, Mohammad Nadir; Arifi, Fatima; Saeedzai, Sayed Ataullah
Highlights: Crimean-Congo Hemorrhagic Fever (CCHF) has significantly increased in Afghanistan during recent years. Those who are exposed to the vector ( Hyalomma ticks ), infected animals, the blood and tissues of freshly slaughtered livestock are most at risk. The cases reach to its peak during Eid-al-Adha when people are sacrificing animals. Information on CCHF pathogen genotypes and lineage, strain movement and sequence diversity of the CCHF in Afghanistan is not known yet. Abstract: Objective: This study aims to provide descriptive epidemiology of human CCHF cases in Afghanistan by demographic, geographical, and seasonal characteristics. Methodology: This paper's findings are based on the retrospective analysis of the National Surveillance System's collected data from 2016 to 2018. Weekly cases exceeding the 90th percentile of the expected number of cases were considered to be exceptional and above normal. Results: The National Surveillance System detected 1, 284 CCHF cases from 2007 to 2018, of which 163 cases were in 2016, 245 cases in 2017 and 483 cases in 2018. A total of 891 suspected and confirmed cases were reported between 2016 and 2018, 293 (33%) of these cases were confirmed by detecting IgM antibody using ELISA and RT-PCR. Among confirmed cases, the three-year case fatality ratio (CFR) was 43.3%. Among the reported cases, 68.5% were males and 31.5% females. The frequent reported occupational groups were housewives (15%), health staff (13%), shepherds (11%), butchers (6%), students (6%), animal dealers and farmers (both 2%) respectively, 19% were unemployed, and occupation was not recorded for 26% of cases. Conclusion: Recently, CCHF has significantly increased in Afghanistan. Despite the increased frequency of cases, the laboratory capacity to test specimens and overall knowledge of CCHF management remains limited.